2014
DOI: 10.1021/jp503038m
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Drug–Model Cell Membrane Interactions Using Sum Frequency Generation Vibrational Spectroscopy: A Case Study of Chlorpromazine

Abstract: Sum frequency generation (SFG) vibrational spectroscopy and attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy were applied to study interactions between an antipsychotic agent, chlorpromazine (CPZ), and model cell membranes consisting of either distearoylphosphatidylcholine (DSPC) or dipalmitoylphosphatidylglycerol (DPPG). The PC and PG lipids represent the zwitterionic and anionic components of the cell membranes, respectively. For an isotopically asymmetric bilayer composed of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 74 publications
0
36
0
Order By: Relevance
“…[31][32][33][34][35][36][37][38][39][40] SFG is a second order nonlinear laser spectroscopy with intrinsic surface/interface sensitivity due to its special selection rule. SFG can provide molecular details on how membrane lipid bilayers interact with various molecules or materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35][36][37][38][39][40] SFG is a second order nonlinear laser spectroscopy with intrinsic surface/interface sensitivity due to its special selection rule. SFG can provide molecular details on how membrane lipid bilayers interact with various molecules or materials.…”
Section: Introductionmentioning
confidence: 99%
“…SFG can provide molecular details on how membrane lipid bilayers interact with various molecules or materials. [31][32][33][34][35][36][37][38][39][40] SFG has been widely applied to study the interactions between lipid bilayers and proteins/peptides such as melittin, 31 tachyplesin I, 32 magainin 2, 33 MSI-78, 34 alamethicin, 35-37 G Protein-Coupled Receptor Kinase 5, 38 and human islet amyloid polypeptide 40 and so on. 41,42 SFG can also detect and monitor the molecular structure and dynamics of both lipids and their interacting molecules in situ in real time without exogenous labeling.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Both I CH 3 and I CD 3 remained unchanged until around 2000 s, suggesting that the flip-flop process of the dDPPC/DPPC bilayer finished in a shorter time as compared with that of the dDSPC/DSPC bilayer. 7 For comparison, the time-dependent SFG signal intensities of I CH 3 and I CD 3 for the dDPPC/DPPC bilayer with the addition of 5 mM memantine were also monitored ( Figure 2B). For a quantitative comparison, all the time-dependent curves in Figure 2 were fitted using a reported method 6,7,50,51 (see details in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…7 For comparison, the time-dependent SFG signal intensities of I CH 3 and I CD 3 for the dDPPC/DPPC bilayer with the addition of 5 mM memantine were also monitored ( Figure 2B). For a quantitative comparison, all the time-dependent curves in Figure 2 were fitted using a reported method 6,7,50,51 (see details in the Supporting Information). The fitting results for the 2875 cm −1 revealed that the flip-flop rate (k) and the half-life (t 1/2 ) of the neat lipid bilayer were (3.6 ± 0.8) × 10 −4 s −1 and (9.6 ± 2.7) × 10 2 s, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Model lipid membranes prepared in the form of supported lipid bilayers (SLBs) [37][38][39][40][41][42][43][44][45][46][47] and giant unilamellar vesicles (GUVs) [48][49][50][51][52][53][54] were applied as the platforms for imaging phase-separated lipid raft domains using confocal fluorescence microscopy.…”
mentioning
confidence: 99%